2004
DOI: 10.1111/j.1741-3737.2004.00021.x
|View full text |Cite
|
Sign up to set email alerts
|

Interethnic Relationships: The Role of Social Network Diversity

Abstract: We examine the degree to which ethnic diversity in social networks relates to the frequency of interethnic romantic relationships for 318 college students. In a multinomial logit, we find that the odds of having an interethnic relationship once or twice, versus never, increase significantly if the respondent has a relatively ethnically diverse friendship network, is male, and supports interethnic dating. The odds of having an interethnic relationship often, versus once or twice, are significantly higher for pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 25 publications
3
58
0
1
Order By: Relevance
“…Neste caso, as redes sociais desempenham um papel fundamental, pois regulam as normas e sancionam os comportamentos não normativos. Assim, a endogamia está mais enfatizada em grupos que querem ou necessitam de manter a coesão grupal, tal como os valores próprios (Clark-Ibañez e Felmlee, 2004;Huijnk et al, 2010;Sniderman e Hagendoorn, 2007). Inclusive, as famí-lias destacadamente conservadoras e com menor nível académico são mais propensas a apresentar atitudes preconceituosas e negativas para o ex-grupo (Lambert e Chasteen, 1997); portanto, entendem o matrimónio homogâmico como um valor em si mesmo.…”
Section: Enquadramento Teóricounclassified
“…Neste caso, as redes sociais desempenham um papel fundamental, pois regulam as normas e sancionam os comportamentos não normativos. Assim, a endogamia está mais enfatizada em grupos que querem ou necessitam de manter a coesão grupal, tal como os valores próprios (Clark-Ibañez e Felmlee, 2004;Huijnk et al, 2010;Sniderman e Hagendoorn, 2007). Inclusive, as famí-lias destacadamente conservadoras e com menor nível académico são mais propensas a apresentar atitudes preconceituosas e negativas para o ex-grupo (Lambert e Chasteen, 1997); portanto, entendem o matrimónio homogâmico como um valor em si mesmo.…”
Section: Enquadramento Teóricounclassified
“…These factors include: length of time in the U.S., low levels of ethnic identification, high levels of English language acculturation, ethnically diverse social networks, and low ingroup bias and intergroup anxiety [26,32,36,37]. Research on rates of actual intercultural dating is mixed.…”
Section: Latino/a Students and Intercultural Datingmentioning
confidence: 99%
“…It was shown in previous studies that ethnic diversity of friendships influences interethnic dating (Clark-Ibáñez & Felmlee 2004, Keels & Harris 2014, and I argued that a possible source of this effect can be the change of preferences. Results supported the hypothesis that having Roma friends increased the probability that non-Roma respondents find their Roma classmates attractive, and also that they would date with Roma classmates.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when analyzing friendship segregation and racial integration in schools, Moody (2001) found that friendship segregation actually increased and not decreased, if group diversity was elevated from low to moderate levels. About the romantic issues, Clark-Ibáñez & Felmlee (2004) found that school diversity did not, only friendship heterogeneity did increase the chance of inter-ethnic dating.…”
Section: Introductionmentioning
confidence: 99%